KEBIJAKAN PERBANKAN DALAM MENENTUKAN JAMINAN PERSEORANGAN SEBAGAI JAMINAN TERHADAP PEMBERIAN KREDIT UMUM BAGI NASABAH (STUDI PADA BANK NTT KCU KUPANG) - Alexsander Reynaldi Koli; Florensiana Resi Ngepi; Stefanus Don Rade (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Banking credit is one of the conventional bank businesses that has been widely used by members of the public who need funds. Law Number 10 of 1998 concerning Banking states that the main function of Indonesian Banking is as a collection and distribution of public funds aimed at supporting the implementation of national development towards improving the welfare of many people. We know two types of credit guarantee rights in practice in the community, namely individual credit guarantee rights (personal guarantee), which is a guarantee of a third party who acts to guarantee the fulfillment of debtor obligations. The research method that the author uses is an empirical juridical research method. 'This research uses a problem approach, a statutory approach (Statute-Approach) and a concept approach (conceptual approach). The data source that the author uses is primary data by means of field research (Field Research) located at Bank NTT.